Learning Video Media in Natural and Social Science Subjects for Fourth-Grade Elementary School - Dewa Nyoman Katon Agastya; I Wayan Sujana (Jurnal Edutech Undiksha, 2023)
The limited learning media that increases students' motivation and interest in learning makes learning less effective. It takes a product that can support learning activities. This study aims to develop Learning Video Media in Class IV Elementary School Science Subjects. This type of research is development research that was developed using the ADDIE development model. Data is processed using a data collection method with a questionnaire and multiple-choice objective tests. The research subjects were subject matter experts, learning design experts, and learning media experts. The test subjects were three students in the individual trial, 6 in the small group trial, and 18 in the effectiveness test. The data analysis technique used is quantitative descriptive analysis and inferential statistics. The research results of the assessment results from experts and students have good and very good categories so that the products developed are feasible or valid to use. The results of the effectiveness test are that there is a significant difference of 5% before and after using this product. Thus the results of this study indicate that Learning Video Media media is valid and effective for use in Class IV Elementary School Science Subjects.